Effectiveness of The Electronic Procurement Service System in Procurement of Goods And Services in Gayo Lues District in 2021 - Siregar*, Iwan Setiawan; Nurhafni, Nurhafni; Muhtarom, Muhtarom (Riwayat: Educational Journal of History and Humanities, 2024)
Public services in government administration must be realized immediately in order to create good governance. E-procurement as a website is an auction system for the procurement of goods and services by the government using internet-based technology, information and communication tools, but the problems that occur with this system are not yet running effectively in terms of timeliness, cost accuracy, choice accuracy and precision. targets and problems of lack of human resource capacity and supporting infrastructure, the grand theory used is timeliness, cost accuracy, choice accuracy and target accuracy. This research uses descriptive qualitative research methods using techniques to obtain data through observation, interviews and documentation. This research used 13 informants who were determined purposively, consisting of the Head of the Goods and Services Procurement Section of the Gayo Lues Regency Government and his staff, e-procurement operators, some participants in the goods/services procurement auction and some residents of the Gayo Lues Regency community. To overcome the various weaknesses that exist in the conventional goods/services procurement process, the government has introduced an innovation in the procurement of goods/services in the public sector, namely e-procurement. E-procurement is a website which is an auction system for the procurement of goods and services by the government using internet-based technology, information and communication tools. The results of the research explain that the effectiveness of the E-Procurement System in Procurement of Goods and Services in the Gayo Lues Regency Government is not yet effective because there are still constraints in infrastructure and human resources which are still lacking, which affects effectiveness in procuring goods and services. The conclusion of this research is the Effectiveness of the E-Procurement System in Procurement of goods and services at the Gayo Lues Regency Government has not been effective, this can be seen from four indicators of effectiveness, namely timeliness, cost accuracy, choice accuracy and target accuracy, as well as obstacles for the Gayo Lues Regency Government in implementing the e-procurement system in the procurement of goods and services. two, namely Human Resource Barriers and Infrastructure Barriers.